The legal capacity of people with Down syndrome to be able to donate organs in Peru - Santome Sánchez, Aldo Alesandro (2019)
This article has carried out a legal-normative analysis on the ability of people with Down Syndrome to express their willingness in case of organ donation in Peru, a work that opens the legal possibility of acceptance of the consent conferred by the giver with Down syndrome. For such a comet, a joint study of Peruvian legislation and international human rights treaties ratified by Peru has been carried out, which promotes an interest in respecting the autonomy of people with some type of disability.